The Efficacy of Moisturisers Containing Ceramide Compared with Other Moisturisers in the Management of Atopic Dermatitis: A Systematic Literature Review and Meta-Analysis - Nugroho, Wisnu Triadi; Sawitri, Sawitri; Astindari, Astindari; Utomo, Budi; Listiawan, M. Yulianto; Ervianti, Evy; Astari, Linda (Indian journal of dermatology, 2023)
Atopic dermatitis (AD), also known as atopic eczema, is a chronic inflammatory skin condition that recurs frequently and has diverse clinical features. The main mechanism of AD is the dysfunction of the skin-epidermal barrier. One of the causes of stratum corneum (SC) structural integrity disruption is the decreased production of ceramide, an important lipid component in SC. The latest generation of moisturisers contain ceramide to help replace this lipid deficit. This study aimed to compare the efficacy of moisturisers containing ceramide with other moisturisers for AD management. Searches were conducted systematically on PubMed, the Cochrane Library, ScienceDirect, Clinicaltrials.gov, and Google Scholar for studies published from January 2012 to July 2022. Interventions and outcomes were compared in this study. Statistical analysis was performed with ReviewManager 5.4 software. Five articles met the eligibility and inclusion criteria. Three articles were meta-analyses on trans-epidermal water loss (TEWL) outcomes and two articles were meta-analyses on SCORing Atopic Dermatitis (SCORAD) outcomes. A meta-analysis of TEWL results found that TEWL values were not significantly different in subjects treated with ceramide-containing moisturisers (mean difference: -3.56, 95% CI [-8.63, 1.52], = 0.17) with high heterogeneity (I = 92%) compared to other treatments. The change in SCORAD was significantly higher in moisturisers containing ceramide (mean difference: -0.98, 95% CI [-1.63, -0.33], = 0.003) with low heterogeneity (I = 0%). Moisturisers containing ceramide improve SCORAD and TEWL; however only the changes in SCORAD in moisturisers containing ceramide is superior to other moisturisers.